Relapsing polychondritis: focus on cardiac involvement - Yin, Ruxue; Zhao, Mengzhu; Xu, Dong; Wang, Qian; Li, Mengtao; Zhang, Wen; Zhang, Fengchun; Zeng, Xiaofeng; Huo, Yuping; Hou, Yong (Frontiers in Immunology, 2023)
Background: Relapsing polychondritis (RP) with cardiac involvement may present with acute cardiovascular events, and may be associated with a negative prognosis.Herein, we analyzed the clinical characteristics of RP patients with cardiac involvement.: RP patients, hospitalized from December 2005 to December 2021 at Peking Union Medical College Hospital (PUMCH), were screened. Univariate and multivariate logistic regression analyses were used to statistically analyze the clinical characteristics of these patients.The incidence of cardiac involvement in inpatients with RP was 24.1%.Univariate logistic regression analysis revealed age, central nervous system (CNS) involvement, neutrophil-to-lymphocyte ratio (NLR) > 6.41, and disease duration > 4 years as risk factors for cardiac involvement in RP. Conversely, the incidence of tracheobronchial and chest wall involvement was significantly lower in the group with cardiac involvement. Multivariate logistic regression confirmed that age, CNS involvement, NLR > 6.41, and disease duration > 4 years were independent factors for cardiac involvement. Subsequently, we identified five well-defined clinical patterns of RP, based on the involvement of different organs in our patients, and found that the heart-brain model was significantly mutually exclusive with the airway model.Occurrence of cardiac involvement in RP is associated with age, CNS involvement, NLR, and disease duration. It is mutually exclusive with airway-related involvement. Regular echocardiography and electrocardiography are necessary for patients with RP.